Qualitative and quantitative approaches of occupational risks agents in a Brazilian facilit (Brazilian Journal of Radiation Sciences, 2018)
The occupational risk assessment is a structured and systematic process, which depends on the correct identification of probable risk factors and agents potentially founded at workplace. The objective of this paper was to carry out the basic characterization of a Brazilian radioisotope production facility through ample knowledge of the workplace, workforce, task performed and identification and evaluation of occupational risk agents in the workplace. The data analysis comprised a qualitative or quantitative approaches based on subjective information obtained by questionnaire, interview and observations about workplace, workforce and risk agents. The workforce was distributed into eight work processes. Regarding task-related exposure there was assumed that all workers presented the same exposure profile. Therefore, it was made an evaluation of the association degree between the occupational risks agents, which there were identified 17 risk agents at the workplace, including physical, chemical, biological, ergonomic and accident risks. Although the workers may be potentially exposed to different risk agents, the ionizing radiation was the main physical risk factor observed in this facility.